Perbedaan Kecurangan Akademik Ditinjau Dari Jenis Kelamin Dan Bidang Ilmu Pada Mahasiswa - Bagus Setiawan, Imam; Imamdotco@gmail.com, S.Psi, M.SI (2017)
Abstrac Cheating (cheating) is one of the educational phenomena that often emerge accompany the activity of the learning process and in the assessment process even to the writing of research. The purpose of this research was to determine differences in academic cheating by gender and field of science in students. The study population is students Surakarta Muhammadiyah University Faculty of Economics and Faculty of Engineering class of 2013-2015. The sampling technique is done with two-stage random cluster, which was first held random faculty which has been divided into the faculty of exact and faculty non-exact, then having obtained the faculty of exact and non-exact random longer courses that exist in both the faculty and the results random obtained faculty inexact: the Faculty of Engineering courses in architectural engineering faculty and non inexact: the Faculty of Economics courses business economics, by way random faculty and random majors researchers got the participants with a total of 156 people, with the subject of the engineering faculty numbered 75 and the subject of faculty economy amounted to 81 with total male subjects amounted to 79 and female subjects amounted to 77. Measuring instruments used is a modification of the scale of academic cheating compiled by Kurniawan (2011) based on aspects of academic cheating proposed by Anderman (2006). The scale consists of 40 academic cheating item, item 24 favorable and 16 unfavorable item. Data analysis technique used is comparative independent sample t-test. Based on the result of the gender, that men are more predisposed academic cheating than women. From the fields of science, the field of exact sciences student has a tendency to commit fraud on a student's academic from non-exact science. Keywords: academic cheating, gender, field of the studies.